Causes of stigma and discrimination associated with tuberculosis in Nepal: a qualitative study - Karki Deepak K; Baral Sushil C; Newell James N (BMC, 2007)
Abstract Background Tuberculosis (TB) is a major cause of death. The condition is highly stigmatised, with considerable discrimination towards sufferers. Although there have been several studies assessing the extent of such discrimination, there is little published research explicitly investigating the causes of the stigma and discrimination associated with TB. The objectives of our research were therefore to take the first steps towards determining the causes of discrimination associated with TB. Methods Data collection was performed in Kathmandu, Nepal. Thirty four in-depth interviews were performed with TB patients, family members of patients, and members of the community. Results Causes of self-discrimination identified included fear of transmitting TB, and avoiding gossip and potential discrimination. Causes of discrimination by members of the general public included: fear of a perceived risk of infection; perceived links between TB and other causes of discrimination, particularly poverty and low caste; perceived links between TB and disreputable behaviour; and perceptions that TB was a divine punishment. Furthermore, some patients felt they were discriminated against by health workers Conclusion A comprehensive package of interventions, tailored to the local context, will be needed to address the multiple causes of discrimination identified: basic population-wide health education is unlikely to be effective.